Prevalence of Female Sexual Dysfunction in Different Pregnancy Trimesters: A Systematic Review and Meta-Analysis - Mina Malary; Mahmood Moosazadeh; Malihe Amerian; Shadi Sabetghadam; Afsaneh Keramat (Guilan University of Medical Sciences, 2022)
Abstract Introduction: Pregnancy is one of the most sensitive periods in a woman's life. Physical and psychological changes during pregnancy can significantly affect the couples' sexual relations. Healthy sexual desire during pregnancy is essential for the development of couples as parents. Objective: This meta-analysis study estimates the prevalence of sexual dysfunction overall and in different trimesters of pregnancy. Materials and Methods: This research is a systematic review and meta-analysis. A search was conducted in PubMed, Scopus, Science Direct, and Google Scholar databases to find cross-sectional and prospective cohort studies investigating the prevalence of sexual dysfunction in different trimesters using the female sexual function index (FSFI) published from 2000 to 2019. The methodological quality of each study was assessed using the modified from the STROBE (The Strengthening the Reporting of Observational Studies in Epidemiology) checklist to determine the risk of bias. The standard error of prevalence in each study was calculated based on the binomial distribution formula. Based on heterogeneity results, a random effect model was used to estimate the prevalence. Results: Fifteen articles met the inclusion criteria, with a total number of 3569 participants, of which 2538 were in cross-sectional studies and 1031 in prospective cohort studies. In the meta-analysis of both prospective cohort and cross-sectional studies, the prevalence rates of sexual dysfunction in the first, second, and third trimesters, and overall were estimated at 51.33% (95%CI; 37.41-65.25), 51.13% (95%CI; 38.93-63.33), 72.80% (95%CI; 65.78-79.81%), and 58.65% (95%CI; 51.50-65.80), respectively. Conclusion: The trimester of pregnancy has a predictive role in the prevalence of sexual dysfunction during pregnancy. The prevalence of sexual dysfunction is higher in the third trimester.